Separation of Scales in Transpiration Effects on Low Flows: A Spatial Analysis in the Hydrological Open Air Laboratory. Issue 9 (10th September 2018) - Széles, B.; Broer, M.; Parajka, J.; Hogan, P.; Eder, A.; Strauss, P.; Blöschl, G.
Abstract: The objective of this study was to understand whether spatial differences in runoff generation mechanisms affect the magnitudes of diurnal streamflow fluctuations during low flow periods and which part of the catchment induces the diurnal streamflow signal. The spatiotemporal variability of the streamflow fluctuations observed at 12 locations in the 66‐ha Hydrological Open Air Laboratory experimental catchment in Austria was explained by differences in the vegetation cover and runoff generation mechanisms. Almost a quarter of the volume associated with diurnal streamflow fluctuations at the catchment outlet was explained by transpiration from vegetation along the tributaries; more than three quarters was due to transpiration by the riparian forest along the main stream. The lag times between radiative forcing and evapotranspiration estimated by a solar radiation‐driven model increased from 3 to 11 hr from spring to autumn. The recession time scales increased from 21 days in spring to 54 days in autumn. Observations and model simulations suggest that a separation of scales in transpiration effects on low flows exists both in time and space; that is, the diurnal streamflow fluctuations are induced by transpiration from the riparian vegetation, while most of the catchment evapotranspiration, such as evapotranspiration from the crop fields further away from the stream, do not influence the diurnal signal in streamflow. Key Points: The amplitude of the diurnal streamflow fluctuations from wetlands was 1 magnitude larger than those from tile drains and springs Three quarters of the volume associated with diurnal streamflow fluctuations was due to riparian transpiration along the main stream Lag times between radiative forcing and ET increased from 3 to 11 hr from spring to autumn